The economic impact of immigration on productivity in Malaysia - Lau, Yien Hee (Universiti Malaysia Sarawak (UNIMAS), 2013)
The main purpose of this study is to investigate ·Tte impact of immigration on productivity in major sector (construction sector and manufacturing sector) of Malaysia, using annual time series data covering the period from 1982 to 2012. Time series analysis applied in this study. In this study, Cobb-Douglas production function is used to derive the model specificatin The conclusions are: first, the significance of the variables in first difference for both construction sector and manufacturing sector reveal that they are stationary in first difference. Second, the results show no-cointegration between the variables in both sectors, which indicates that there is no strong evidence for long tenn relationship. Third, through Granger causality test, the results reveal that there is bidirectional causality in manufacturing sector and no causality existing in construction sector. This means that there is a positive impact of migrant labors on labor productivity in manufacturing sector. On the other hand, construction sector is much more depending on domestic labors in Malaysia .. Some policies have been recommended in this study that could be carried out by the government to support the sustainable economic development in the future.